2017
DOI: 10.1002/ejp.1123
|View full text |Cite
|
Sign up to set email alerts
|

Chronic musculoskeletal pain in European older adults: Cross‐national and gender differences

Abstract: This study provides epidemiological data of chronic musculoskeletal pain in older adults. Reported differences contribute to highlight the relevance of considering a gender perspective in chronic musculoskeletal pain research. Cross-national comparison also offers a map of differences that improves the knowledge of this chronic condition in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
70
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 48 publications
(64 reference statements)
18
70
0
5
Order By: Relevance
“…The most consistent risk factor observed in the studies was the female sex, which was previously reported as a risk factor for musculoskeletal pain in musicians in studies with heterogeneous groups, presenting a higher prevalence and a longer duration of symptoms [29][30][31]. Female patients also show more sites of pain and more severe pain in those with chronic musculoskeletal pain [32], corroborating with previous studies that found higher prevalence rates among female than male patients [31][32][33]. The definite mechanism underpinning the association between female sex and higher prevalence of the musculoskeletal pain remains poorly understood.…”
Section: Discussionsupporting
confidence: 64%
“…The most consistent risk factor observed in the studies was the female sex, which was previously reported as a risk factor for musculoskeletal pain in musicians in studies with heterogeneous groups, presenting a higher prevalence and a longer duration of symptoms [29][30][31]. Female patients also show more sites of pain and more severe pain in those with chronic musculoskeletal pain [32], corroborating with previous studies that found higher prevalence rates among female than male patients [31][32][33]. The definite mechanism underpinning the association between female sex and higher prevalence of the musculoskeletal pain remains poorly understood.…”
Section: Discussionsupporting
confidence: 64%
“…There was a predominance of women (14 women, 6 men) among the participants which can be viewed as a limitation. However, this type of pain is known to be more prevalent in one or multiple locations, and experienced as disabling to a greater extent by women than by men (Cimas et al 2018;Jackson et al 2016;Patel et al 2013;Rottenberg et al 2015). Another potential limitation in this study might be that the years living with pain are not described.…”
Section: Methodological Considerationsmentioning
confidence: 93%
“…Long-term musculoskeletal pain caused by musculoskeletal conditions is a global, pervasive and predominant health problem. It causes difficulties, independence, and disabilities (physical, psychological, social and existential) in daily life (Blyth et al 2019;Cimas et al 2018;Hoyos et al 2018;Smith et al 2019;Stubbs et al 2014) with significant impact on an older adult´s sense of well-being and quality in life. Research shows that as many as 60-80% of 65-year-older adults have at least one musculoskeletal condition with potential to cause pain (Duncan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Falls are much more prevalent in older people with pain than in those without pain [4]. Recent epidemiological data out of Europe shows that chronic musculoskeletal pain is very frequent in older adults [1]. Therefore, any intervention that reduces pain intensity should be accompanied by a reduction in the rate of falls in older people.…”
Section: Discussionmentioning
confidence: 99%
“…The global population is ageing, as exemplified by recent Eurostat population data which estimates that the population of people aged 65 years and older will increase from 18% in 2013 to 28% in 2060 [1]. Ageing increases the risk of escalating morbidity (people living longer in poor health) [2].…”
Section: Introductionmentioning
confidence: 99%